2004
DOI: 10.1128/aem.70.12.7110-7118.2004
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces coelicolor A3(2) Lacks a Genomic Island Present in the Chromosome of Streptomyces lividans 66

Abstract: Streptomyces lividans ZX1 has become a preferred host for DNA cloning in Streptomyces species over its progenitor, the wild-type strain 66 (stock number 1326 from the John Innes Center collection), especially when stable DNA is crucial for in vitro electrophoresis, because DNA from strain 66 contains a novel modification that makes it sensitive to oxidative double-strand cleavage during electrophoresis. Detailed analysis of this modification-deficient mutant (ZX1) revealed that it has several additional phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…However, studies on Streptomyces (He et al, 2007;Zhou et al, 2004) suggested that absence of the genes was the more likely explanation. Therefore, we designed primers P1 and P2 to amplify a 484 bp region of dndC (MAB_1095) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies on Streptomyces (He et al, 2007;Zhou et al, 2004) suggested that absence of the genes was the more likely explanation. Therefore, we designed primers P1 and P2 to amplify a 484 bp region of dndC (MAB_1095) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, Wallace et al (1993) reported that over 40 % of clinical isolates of M. abscessus were untypable by PFGE due to degradation of the DNA, also known as DNA smearing. The phenomenon of DNA degradation (Dnd) during PFGE occurs with other species of bacteria (Corkill et al, 2000;Ou et al, 2009;Yao et al, 2009), and much of our understanding of the underlying mechanism stems from analyses of natural variants and recombinant strains of Streptomyces that differ in Dnd phenotype (Chen et al, 2010;Dyson & Evans, 1998;Ou et al, 2009;Zhou et al, 1988Zhou et al, , 2004Zhou et al, , 2005. DNA from Streptomyces lividans, but not from Streptomyces coelicolor A3(2), exhibits site-specific degradation in some preparations of Tris buffer during electrophoresis, and it was discovered that this technical problem can be resolved by adding thiourea to the gel running buffer (Chen et al, 2010;Ray et al, 1992Ray et al, , 1995Zhou et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Specifically Streptomyces lividans is an important member of this family, because it is nonpathogenic filamentous bacteria and there is substantial knowledge about its genetic manipulation. 8 In fact, this organism is able to produce large amounts of extracellular proteins, and is often used for cloning, expression, and production of heterologous proteins. [9][10][11] The Mycobacterium tuberculosis genes point to explore effective prevention and treatment means.…”
Section: Introductionmentioning
confidence: 99%
“…When transformed into ZX1, cosmid 16C3 (ZX1::16C3) could restore the Dnd phenotype of mutant ZX1, indicating that 16C3 harbored genes associated with the DNA modification. By subsequent sub-cloning and Dnd phenotypic tests, a 6,665 bp dnd locus containing five dnd genes was precisely localized on cosmid 16C3 [11]. , dndD (lane 6) and dndE (lane 7) can abolish the Dnd phenotype, whereas the mutation of dndB (lane 4) aggravates the degradation.…”
Section: The Dnd Gene Cluster Is Responsible For Phosphorothioationmentioning
confidence: 99%